Tourists' Experiences with Smart Tourism Technology at Smart Destinations and Their Behavior Intentions. (November 2020) - Jeong, Miyoung; Shin, Hyejo Hailey
This study attempts to assess how tourists use smart tourism technologies at destinations and measure the effects of STT usage on overall travel experience and future revisit intention. Although STTs have received growing attention, little research has evaluated tourists' experience with STTs available at various smart tourism destinations and potential consequences. Building on studies on online tourism information sources, this study develops a conceptual framework to test hypotheses related to STT experiences and consequences. Based on an online survey with travelers to top five US smart cities, this study classifies the most frequently used STTs and examines tourists' overall experience and satisfaction with STTs as well as their revisit intention. Findings suggest that three attributes of STTs—informativeness, interactivity, and personalization—are the key factors affecting tourists' experience, satisfaction, and revisit intentions. The level of perceived security/privacy moderates the relationships between three STT attributes and tourists' memorable experience.